New species and revalidations of scarab beetles (Coleoptera: Geotrupidae: Athyreini and Coleoptera: Scarabaeidae: Scarabaeinae) from Costa Rica and Panama - Kohlmann, Bert; Solís, Ángel (Zootaxa, 2012)
The following new species of geotrupids and scarabs from Costa Rica and Panama are described: Athyreus gulesserianinew species, Ateuchus alutacius new species (the first recorded brachypterous Ateuchus species), Coprophanaeus geph-yra new species, Deltochilum acanthus new species, and Onthophagus turgidus new species. The following two speciesof Coprophanaeus are revalidated: C. kohlmanni Arnaud and C. uhleri Malý & Pokorný. Illustrations of the dorsal habitus of the new species are provided, as well as distribution maps for all species.